2013
DOI: 10.1111/dpr.12019
|View full text |Cite
|
Sign up to set email alerts
|

Improving Transparency and Accountability in the Budget Process: An Assessment of Recent Initiatives

Abstract: In recent decades budget transparency has come to be seen as a pillar of good governance. This article reviews budget‐related transparency and accountability initiatives (TAIs) to analyse their impact. While there are many examples of success in terms of budget processes around the world being opened up to greater participation and scrutiny, there is no single recipe for creating a successful initiative to enhance transparency and accountability in the budget process. A consistent set of factors does, however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 30 publications
0
40
0
12
Order By: Relevance
“…Based on research conducted by Kaufmann &Kraay (2008), andCarlitz (2013), showed that increasing transparency and accountability in the budgeting process has positive impact on government performance. According to Carlitz, (2013) Based on empirical research, participation, transparency, and accountability have significant influence on the quality of local government budget.…”
Section: H2mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on research conducted by Kaufmann &Kraay (2008), andCarlitz (2013), showed that increasing transparency and accountability in the budgeting process has positive impact on government performance. According to Carlitz, (2013) Based on empirical research, participation, transparency, and accountability have significant influence on the quality of local government budget.…”
Section: H2mentioning
confidence: 99%
“…According to Carlitz, (2013) Based on empirical research, participation, transparency, and accountability have significant influence on the quality of local government budget. Based on the above theory and viewpoints, the hypotheses for this research are as follows:…”
Section: H2mentioning
confidence: 99%
“…Performancebased financial management requires that the direction of the use of government funds is no longer merely output oriented but further strengthening the outcomes. Performance-based budgeting, in addition to outcome orientation, is also important to create accountability to the public (Murdiati, 2014), as well as a pillar of good governance practice (Carlitz, 2013).…”
mentioning
confidence: 99%
“…This positive framing of accountability has fuelled the drive to strengthen accountability institutions which, it is believed, will fast-track socio-economic development, particularly in developing countries. The interest in accountability is expressed in policy discourses, academic writings, reform initiatives, and within the international community which is led by the International Monetary Fund (IMF) and the World Bank (WB) in Africa (Andrew, 2013;Booth, 2011;Bratton and Logan, 2014;Grindle, 2010;Hyden, 2013;Kelsall, 2008;Lindberg, 2010;Melber, 2007;Transparency International, 2014;Walle, 2009;WB, 2004) as well as in Tanzania (Bratton, 2010;Carlitz, 2013;Heilman and Ndumbaro, 2002;Hoffman, 2010;Hyden, 2010;Khan and Gray, 2006;Kelsall, 2003;Kersall and Muya, 2004;Killian, 2014;Lawson and Rakner, 2005;Lindner and Banoba, 2014;Mallya, 2011;Matenge, 2012;Mwakyembe, 1985;Rottenburg, 2002;Schatz, 2013;Shivji et al, 2004;Tambila, 2004;Therkildsen, 2000;Tilley, 2014;Tsubura, 2014).…”
Section: Rethinking Accountability In the Context Of Governmentalitymentioning
confidence: 99%
“…However, little is known about various guises of informal accountability and about how they interact with and relate to formal accountability. Many accountability studies in Tanzania have generally focused on political accountability at the local level (Hoffman, 2006;Lawson and Rakner, 2005;Maluka, 2011;Venugopal and Yilmaz, 2010) and the national level (Andrew, 2013;Carlitz 2013;De Mesquita and Smith, 2012;Grindle, 2010;Khan and Gray 2006;Hyden, 2010;Kersall, 2003;Kersall and Muya, 2004;Lawson and Rakner, 2005;Mallya, 2011;Matenge, 2012;Rioba, 2012;Tilley, 2014;Tsubura, 2014) and hardly on the water sector, particularly on the rural water supply sector.…”
Section: Alternative Views To Accountability Practicesmentioning
confidence: 99%